ANALISIS DAN INTEGRASI KEARIFAN LOCAL LUBUK LARANGAN TANTANG SAKTI DALAM PEMBELAJARAN SAINS - Jufrida, Jufrida; Basuki, Fibrika Rahmat; Destinanda, Anggun (EduFisika: Jurnal Pendidikan Fisika, 2020)
The research aims to analyze the concept of science that was found in local wisdom, and integrate local wisdom into the science of the sciences. This research is a qualitative descriptive study. The subject in this study was the community figure of Suban Village and science education expert. Data collection was done through interviews and documentation. Data was analyzed descriptively. Lubuk Larangan â€œTantang Saktiâ€ is the local wisdom of Suban village in preserving of fish and watershed. Lubuk Larangan is a watershed area that has been agreed by the community and traditional institutions that regulate the prohibition of fishing in the river. Lubuk Larangan â€œTantang Saktiâ€ becomes a conservation area for kapiat/lampam fish (Barbonymus schwanenfeldii). Lubuk Larangan can be integrated in science learning on the topics of environmental conservation, ecosystems, and fluids.